1998
DOI: 10.1002/(sici)1096-8628(19980113)75:2<126::aid-ajmg2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Classification and birth prevalence of orofacial clefts

Abstract: To determine the proportion and birth prevalence of "typical" orofacial clefts (cleft lip (CL), cleft palate (CP), cleft lip and palate (CLP)) and "atypical" clefts (median, transversal, or oblique facial clefts) and the conditions in which they occur, we analyzed a population-based sample of 4,433 cases ascertained from 2,509,881 California births. We classified cases into: isolated cleft anomalies, sequences of the primary defect, chromosomal aberrations, monogenic syndromes, results of known teratogens, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
206
2
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(234 citation statements)
references
References 38 publications
(18 reference statements)
12
206
2
14
Order By: Relevance
“…Cleft palate with intact lip is the most difficult type of craniofacial malformation to diagnose prenatally; in this study, there were 10 fetuses with orofacial clefts that were not prenatally diagnosed, including 6 with cleft palate, 1 with cleft lip, 2 with unilateral CL/P, and 1 with bilateral CL/P. CL/P presents as an isolated finding or part of a complex of multiple congenital anomalies of unknown etiology [11]. The reported incidence of isolated cleft is 32%-58%, and the associated malformation rate is 42%-68% [1,4,5,12] (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Cleft palate with intact lip is the most difficult type of craniofacial malformation to diagnose prenatally; in this study, there were 10 fetuses with orofacial clefts that were not prenatally diagnosed, including 6 with cleft palate, 1 with cleft lip, 2 with unilateral CL/P, and 1 with bilateral CL/P. CL/P presents as an isolated finding or part of a complex of multiple congenital anomalies of unknown etiology [11]. The reported incidence of isolated cleft is 32%-58%, and the associated malformation rate is 42%-68% [1,4,5,12] (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Use of the two sources gave an estimate of 31% of cases having accompanying defects, higher than most studies, but lower than others [9,10]. There was very little overlap in the two sources, indicating that accompanying defects were probably under-ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the estimated occurrence of cleft palate with accompanying defects is 25% or less; [1][2][3][4][5][6] but other studies have reported 45% up to 70% [7][8][9][10] A few specific combinations of defects are known, such as the Pierre Robin Sequence, but most combinations are not recognized as specific syndromes [11]. Still, cases with multiple defects are often called ''syndromic'' cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although cleft lip and palate are distinct and separate congenital abnormalities, they often occur concomitantly. 2 These deformities occur when mesenchymal connective tissues from different embryologic structures fail to meet and merge with each other.…”
mentioning
confidence: 99%